Prototype Pintu Otomatis dan Sistem Alarm Kebakaran Berbasis Internet Of Things - Donny Adams; Yo Ceng Giap (Komunitas Dosen Indonesia, 2024)
This research discusses the development of a prototype of an automatic door and fire alarm system based on the Internet of Things (IoT) utilizing IR sensors to detect people, servo motors to automate door opening, flame detectors for fire detection, MQ-2 sensors for smoke detection, and Telegram as a notification medium. The integration of these technologies aims to enhance security and automation in home or office environments. IR sensors are used to detect people approaching the door, while servo motors provide a solution for door automation. Flame detectors and MQ-2 are employed to detect potential fires by issuing early warnings. This system communicates through the Telegram application to notify users. Testing conducted indicates that IR sensors can detect the presence of people up to a distance of 5cm to activate the micro servo opening the door. The flame detector effectively detects fire up to a distance of 30cm, while the MQ-2 sensor detects smoke up to a distance of 20cm; both generate output signals to activate the micro servo, LED, and buzzer for fire alarms, as well as sending notifications via Telegram to the building owner. With this approach, it is hoped to create an effective, efficient, and reliable system to enhance security and response to emergency situations.